A fiber-reinforced ultra-high performance concrete

Through the modification of steel fibers and the introduction of modified polyester fiber, the problem of uneven distribution of steel fibers and insufficient interface bonding performance were solved, and the mechanical properties and high temperature performance of ultra -high -performance concrete were significantly improved.

CN118894694BActive Publication Date: 2025-01-24THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +3
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411146132.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-01-24
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

In existing ultra-high performance concrete, the uneven distribution of steel fibers and prone to clumping problems lead to low utilization, reduced fluidity and increased cost, while insufficient interfacial bonding performance affects the mechanical properties.

Method used

By modifying the steel fiber, hyperbranched epoxy resin and gallic acid are used to graft chitosan-modified polyester fiber to improve the interface bonding performance between the steel fiber and the matrix, and introduce flexible modified polyester fiber to Replace some steel fibers.

Benefits of technology

It significantly improves the compressive strength, bending strength, fracture energy and high temperature residual properties of concrete, reduce the amount of steel fiber, and prolong the service life of the concrete structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118894694B_ABST
    Figure CN118894694B_ABST
Patent Text Reader

Abstract

The invention discloses a fiber-reinforced ultra-high performance concrete, belongs to the technical field of concrete, and the fiber-reinforced ultra-high performance concrete provided by the invention comprises, by weight, 400-600 parts of coarse aggregate, 600-800 parts of fine aggregate, 80-200 parts of silica fume, 500-800 parts of cement, 100-200 parts of fly ash, 150-250 parts of modified steel fiber, 20-60 parts of modified polyester fiber, 15-40 parts of water reducer and 150-200 parts of water. The present invention reduces the usage of steel fiber by modifying steel fiber and introducing flexible modified polyester fiber, greatly reduces the problems of easy agglomeration and uneven distribution of steel fiber by improving the interfacial bonding performance between steel fiber and matrix, and significantly improves the compressive strength, flexural tensile strength, fracture energy and high temperature residual performance of concrete matrix.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, in particular to a fiber-reinforced ultra-high performance concrete. Background Art

[0002] Concrete is a widely used civil construction material in recent years. With the continuous improvement of construction requirements and the invention and application of high-efficiency water-reducing agents, aggregates and fiber materials, concrete materials have gradually developed towards ultra-high performance concrete (UHPC). Ultra-high performance concrete is an ultra-high strength cement-based material with ultra-high strength, high toughness and low porosity. Because it needs to be mixed with steel fibers, glass fibers, etc., it is also called ultra-high performance fiber reinforced concrete. UHPC will inevitably produce cracks during the tensile process, and the many fibers distributed in the cracks that pass through the cracks play an important role in bridging and transferring tensile stress. The bonding performance of the fiber and matrix interface is one of the most important factors affecting the interface stress transfer mechanism.

[0003] Among all types of fibers, steel fibers have a higher elastic modulus, which shows obvious advantages in restraining crack expansion and transferring loads. They are currently the most widely used fibers in UHPC. However, the distribution of steel fibers in concrete is random and disorderly, with low utilization rate. Although a large amount of steel fibers can enhance its mechanical properties within a certain range, it can also cause the fluidity of concrete to decrease, greatly increasing costs. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a fiber-reinforced ultra-high performance concrete, by modifying the steel fibers and introducing flexible modified polyester fibers, the amount of steel fibers used is reduced, and by improving the interfacial bonding properties between the steel fibers and the matrix, the problems of easy agglomeration and uneven distribution of the steel fibers are greatly reduced, and the compressive strength, flexural tensile strength, fracture energy and high-temperature residual performance of the concrete matrix are significantly improved.

[0005] The technical scheme for achieving the purpose of the present invention is as follows: a fiber-reinforced ultra-high performance concrete, characterized in that, by weight, the raw materials include 400-600 parts of coarse aggregate, 600-800 parts of fine aggregate, 80-200 parts of silica fume, 500-800 parts of cement, 100-200 parts of fly ash, 150-250 parts of modified steel fiber, 20-60 parts of modified polyester fiber, 15-40 parts of water reducer and 150-200 parts of water; the modified steel fiber is a hyperbranched epoxy resin modified steel fiber, and the modified polyester fiber is a gallic acid grafted chitosan modified polyester fiber.

[0006] The modified steel fiber preparation method comprises the following steps: S1. cleaning the steel fiber and drying it, and performing sandblasting on the surface; S2. adding an aminosilane coupling agent to a mixed solution of ethanol and water and stirring evenly, adding the steel fiber obtained in step S1 to the solution and stirring it in a water bath at 70 to 90° C. for 30 to 40 minutes, filtering it and drying it to obtain the silane-modified steel fiber; S3. dissolving citric acid and maleic anhydride in a mixed solution of toluene and 1,4-dioxane under a nitrogen atmosphere, adding p-toluenesulfonic acid to the mixed solution; The acid is stirred at 80-95°C for 2-6 hours to obtain a solution containing citric acid maleate, and p-toluenesulfonic acid is removed by reduced pressure distillation; S4. Epoxy resin is added to the solution of citric acid maleate, the temperature is controlled at 115-120°C, and stirred for 3-4 hours to obtain a hyperbranched epoxy resin; S5. Silane-modified steel fiber is added to the hyperbranched epoxy resin, and stirring is continued for 20-40 minutes; the temperature is lowered to 80-100°C, a curing agent is added, and the modified steel fiber is obtained after stirring for 10-60 minutes;

[0007] The modified polyester fiber preparation method comprises the following steps: S1. dissolving chitosan in an acetic acid solution at room temperature and stirring for 1 to 3 hours, adding an ethanol solution of gallic acid and a catalyst and continuing stirring for 5 to 10 hours to obtain gallic acid grafted chitosan; S2. adding polyester fiber to the reaction solution of gallic acid grafted chitosan, stirring at 170 to 180° C. for 20 to 60 minutes, cooling to room temperature, filtering and drying to obtain the modified polyester fiber.

[0008] Preferably, the steel fiber is composed of a mixture of straight steel fiber and end hook steel fiber in a mass ratio of (3-6): (4-7); the length of the straight steel fiber and the end hook steel fiber is 13-20 mm. Preferably, a mixture of 13 mm straight steel fiber and 20 mm end hook steel fiber in a mass ratio of 5:5 or a mixture of 13 mm end hook steel fiber and 20 mm straight steel fiber in a mass ratio of 5:5.

[0009] Preferably, the sandblasting treatment selects steel shots with a particle size of 0.5-1.5 mm as abrasives; the surface roughness Ra of the steel fiber after sandblasting is 3-6.

[0010] Preferably, the mass ratio of the citric acid, maleic anhydride and bisphenol A epoxy resin is (3.9-5.9):1:(13.8-20.9).

[0011] Preferably, the catalysts used in the reaction of chitosan and gallic acid are 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide; the curing agent is diaminodiphenylmethane; and the epoxy resin is bisphenol A epoxy resin.

[0012] In a specific embodiment, the mass ratio of aminosilane coupling agent to steel fiber is (1-10):100.

[0013] In a specific embodiment, the mass ratio of toluene to 1,4-dioxane in the mixed solution of toluene and 1,4-dioxane is (3-2): (3-2).

[0014] In a specific embodiment, the mass ratio of the epoxy resin to the curing agent is 100:(6-10).

[0015] Preferably, the polyester fiber has a diameter of 10 to 30 μm and a length of 6 to 12 mm.

[0016] Preferably, the mass ratio of chitosan to gallic acid is 1:(0.5-0.8).

[0017] Preferably, the mass ratio of the modified steel fiber to the modified polyester fiber is (4-5):1.

[0018] Preferably, the water reducing agent is a polycarboxylic acid high-efficiency water reducing agent, with a solid content of ≥40% and a water reducing rate of ≥30%; and the cement is ordinary Portland cement.

[0019] Another object of the present application is to provide a method for preparing fiber-reinforced ultra-high performance concrete, comprising the following steps: adding cement, fly ash, silica fume and 20% water and stirring at a speed of 48 r / min for 2 minutes, then adding coarse aggregate and fine aggregate and stirring for 2 minutes, then adding a water reducer and the remaining water and stirring for 3 minutes, and finally adding modified steel fiber and modified polyester fiber and continuing to stir for 3 minutes, and discharging.

[0020] Beneficial Effects

[0021] The present invention provides a fiber-reinforced ultra-high performance concrete having the following beneficial effects: (1) By preparing a hyperbranched epoxy resin and then grafting it onto a steel fiber modified by a silane coupling agent, the hyperbranched modification of the steel fiber is achieved, the interfacial bonding performance between the steel fiber and the cementitious material is greatly improved, the problem of easy agglomeration and uneven distribution of the steel fiber is reduced, the corrosion resistance of the steel fiber is improved, and the compressive strength, flexural tensile strength, fracture energy and high-temperature residual performance of the concrete are improved, and the service life of the concrete structure is extended. (2) The introduction of flexible modified polyester fiber to replace part of the steel fiber can effectively limit the expansion of micro cracks inside the concrete, and improve the compressive strength, flexural tensile strength, fracture energy and high-temperature residual performance of the concrete. Among them, chitosan and gallic acid are first generated by Bloch reaction to form gallic acid-grafted chitosan and then modified into polyester fiber. Gallic acid is beneficial to the formation of a firm and lasting interface bonding of polyester fiber on the surface of cementitious material matrix, while the gelling properties of chitosan can utilize the good fiber morphology, softness and mechanical strength of chitosan to improve the compressive strength, flexural strength, fracture energy and high-temperature residual performance of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The synthetic route of the hyperbranched epoxy resin of the present invention;

[0023] Figure 2 is the H NMR spectrum of citrate maleate of the present invention;

[0024] Figure 3 The synthesis route of the gallic acid grafted chitosan of the present invention;

[0025] Figure 4 The infrared spectra of chitosan and gallic acid grafted chitosan of the present invention are shown in FIG. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0028] The raw materials used in the embodiments and comparative examples are described as follows:

[0029] Coarse aggregate: diabase crushed stone, produced in Ganzhou City, Jiangxi Province.

[0030] Fine aggregate: machine-made sand, with a fineness modulus of 2.8, produced in Qingyuan, Guangdong.

[0031] Citric acid: commercially available from Huiyuan Environmental Protection Technology Co., Ltd.

[0032] Maleic anhydride: commercially available from Shandong Longhui Chemical Co., Ltd.

[0033] Gallic acid: Commercially available, purchased from Zhangjiajie Jiurui Biotechnology Co., Ltd.

[0034] Aminosilane coupling agent: γ-aminopropyltriethoxysilane, commercially available.

[0035] Chitosan: commercially available, industrial grade chitosan, deacetylation degree > 80%, viscosity < 200 mPa.s, purchased from Shandong Aokang Biotechnology Co., Ltd.

[0036] Epoxy resin: bisphenol A epoxy resin, CAS No.: 25085-99-8, Hubei Changxinsheng Chemical Co., Ltd.

[0037] Steel fiber: straight steel fiber was purchased from Yixing Junwei Metal Fiber Co., Ltd.; end hook steel fiber was purchased from Suzhou Yujian Steel Fiber Co., Ltd.

[0038] Steel fiber 1: 13mm straight steel fiber and 20mm end hook-shaped steel fiber, with a mass ratio of 5:5.

[0039] Steel fiber 2: 13mm hook-end steel fiber and 20mm straight steel fiber, with a mass ratio of 5:5.

[0040] Steel fiber 3: 13mm straight steel fiber and 20mm end hook-shaped steel fiber, with a mass ratio of 7:3.

[0041] Steel fiber 4: 13mm straight steel fiber and 20mm end hook-shaped steel fiber, with a mass ratio of 4:6.

[0042] Modified steel fiber 1: Homemade, the preparation method is as follows: S1. Weigh 100 parts by weight of steel fiber 1, clean it and dry it, arrange it neatly and then sandblast it on the surface; S2. Weigh 10 parts by weight of γ-aminopropyltriethoxysilane and add it to 150 parts by weight of 90% ethanol solution and stir it evenly, add acetic acid to adjust the pH of the solution to 3.5-4.0, stir at room temperature for 15 minutes, add the steel fiber obtained in step S1 to the solution and stir it in a water bath at 80°C for 30 minutes, filter to remove the liquid, and put the solid phase into a constant temperature drying oven at 80°C to dry to obtain silane-modified steel fiber; S3. Weigh 17.3 parts by weight of citric acid, 4.4 parts by weight of 1. 0.2 parts by weight of p-toluenesulfonic acid is added to a reactor and blended, and the mixture is stirred and reacted at 80° C. for 30 minutes to obtain a solution containing citric acid maleate. S4. 91.8 parts by weight of bisphenol A type epoxy resin is added to the solution of citric acid maleate, and the temperature is controlled to be stirred and reacted at 120° C. for 30 minutes to obtain a hyperbranched epoxy resin. S5. silane-modified steel fiber is added to the hyperbranched epoxy resin, and stirring is continued for 30 minutes. The temperature is lowered to 100° C., 8 parts by weight of a curing agent is added, and the mixture is stirred for 60 minutes to obtain a modified steel fiber 1. Figure 2 of 1 H NMR characterization results showed the synthesis of citrate maleate.

[0043] Modified steel fiber 2: homemade, the preparation method is similar to that of modified steel fiber 1, except that steel fiber 1 is replaced by steel fiber 2.

[0044] Modified steel fiber 3: homemade, the preparation method is similar to that of modified steel fiber 1, except that steel fiber 1 is replaced by steel fiber 3.

[0045] Modified steel fiber 4: homemade, the preparation method is similar to that of modified steel fiber 1, except that steel fiber 1 is replaced by steel fiber 4.

[0046] Modified steel fiber 5: Homemade, the preparation method is as follows: S1. Weigh 100 parts by weight of steel fiber 1, clean it and dry it, arrange it neatly and then sandblast it on the surface; S2. Weigh 10 parts by weight of γ-aminopropyltriethoxysilane and add it to 150 parts by weight of 90% ethanol solution and stir it evenly, add acetic acid to adjust the pH of the solution to 3.5-4.0, stir at room temperature for 15 minutes, add the steel fiber obtained in step S1 to the solution and stir it in a water bath at 80°C for 30 minutes, filter to remove the liquid, and put the solid phase into a constant temperature drying oven at 80°C to dry to obtain silane-modified steel fiber; S3. Weigh 18 parts by weight of citric acid and add 100 parts by weight of bisphenol A epoxy resin, control the temperature to stir and react at 120°C for 30 minutes to obtain branched epoxy resin; S5. Add silane-modified steel fiber to the branched epoxy resin, continue stirring for 30 minutes, cool to 100°C, add curing agent, and stir for 60 minutes to obtain modified steel fiber 5.

[0047] Modified steel fiber 6: homemade, the preparation method is similar to that of modified steel fiber 1, except that the steel fiber is not subjected to surface sandblasting treatment.

[0048] Modified steel fiber 7: Homemade, the preparation method is similar to that of modified steel fiber 1, except that the surface of the steel fiber is not subjected to silane modification.

[0049] Modified steel fiber 8: homemade, the preparation method is as follows: S1. Weigh 100 parts by weight of steel fiber 1, clean it and dry it, arrange it neatly and then sandblast it; S2. Weigh 10 parts by weight of γ-aminopropyltriethoxysilane and add it to 150 parts by weight of 90% ethanol solution and stir it evenly, add acetic acid to adjust the pH of the solution to 3.5-4.0, stir it at room temperature for 15 minutes, then add the steel fiber obtained in step S1 to the solution and stir it in a water bath at 80°C for 30 minutes, filter to remove the liquid, and put the solid phase into a constant temperature dryer at 80°C. Dry in a drying oven to obtain silane-modified steel fiber; S3. Weigh 18 parts by weight of citric acid and 5 parts by weight of maleic anhydride, dissolve them in 60 parts by weight of toluene and 40 parts by weight of 1,4-dioxane, add 0.2 parts by weight of p-toluenesulfonic acid into the reactor and blend, stir and react at 80°C for 30 minutes to obtain a solution containing citric acid maleate, S4. Add silane-modified steel fiber to the solution of citric acid maleate, continue stirring for 30 minutes, cool to 100°C, add curing agent, and stir for 60 minutes to obtain modified steel fiber 8.

[0050] Polyester fiber 1: 20 μm in diameter, 6 mm in length, purchased from Jiangsu Haide New Materials Co., Ltd.

[0051] Polyester fiber 2: 20 μm in diameter and 12 mm in length, purchased from Jiangsu Haide New Materials Co., Ltd.

[0052] Modified polyester fiber 1: Homemade, the preparation method is as follows: S1. Weigh 20 parts by weight of chitosan and dissolve it in 50 parts by weight of 2% acetic acid solution at room temperature and stir for 3 hours, weigh 10.6 parts by weight of gallic acid and dissolve it in 50 parts by weight of ethanol, add 0.1 parts by weight of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.1 parts by weight of N-hydroxysuccinimide, and stir for 10 hours to obtain gallic acid grafted chitosan; S2. Add 50 parts by weight of polyester fiber 1 to the reaction solution of gallic acid grafted chitosan and stir at 100-150°C for 60 minutes; after cooling to room temperature, filter out the solution, and place the solid in a 60°C oven to dry for 24 hours to obtain modified polyester fiber 1. Figure 4 The figure shows the infrared spectra comparison of chitosan and gallic acid grafted chitosan.

[0053] Modified polyester fiber 2: homemade, the preparation method is similar to that of modified polyester fiber 1, except that polyester fiber 1 is replaced by polyester fiber 2.

[0054] Modified polyester fiber 3: homemade, the preparation method is similar to that of modified polyester fiber 1, except that the weight portion of gallic acid is 15.9 weight portions.

[0055] Modified polyester fiber 4: homemade, the preparation method is similar to that of modified polyester fiber 1, except that the weight portion of gallic acid is 5.3 weight portions.

[0056] Modified polyester fiber 5: homemade, the preparation method is similar to that of modified polyester fiber 1, except that the weight portion of gallic acid is 21.1 weight portions.

[0057] Silica fume: silicon content is more than 94%, semi-densified, purchased from Dongguan Jusan Industrial Co., Ltd.

[0058] Fly ash: The fly ash is first-grade fly ash from power plants, Guangzhou Hengyun Thermal Power Co., Ltd.

[0059] Water reducer: polycarboxylic acid high-efficiency water reducer, purchased from Sika (China) Co., Ltd.

[0060] Cement: P.Ⅱ52.5R silicate cement, purchased from Yingde Conch Cement.

[0061] Water: Dongguan tap water, in line with the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006).

[0062] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0063] Examples 1 to 13

[0064] A fiber-reinforced ultra-high performance concrete, the preparation method of which comprises the following steps: adding cement, fly ash, silica fume and 20% water and stirring at a speed of 48 r / min for 2 minutes, then adding coarse aggregate and fine aggregate and stirring for 2 minutes, then adding a water reducer and the remaining water and stirring for 3 minutes, finally adding modified steel fiber and modified polyester fiber and continuing to stir for 3 minutes, discharging, pouring and vibrating to form, immediately covering with a plastic film and placing at room temperature for 24 hours, and after demolding, wrapping the test block with a geotextile and sprinkling water for curing for 28 days. The specific formula is shown in Table 1.

[0065] Table 1 Fiber-reinforced ultra-high performance concrete (parts by weight)

[0066]

[0067]

[0068] Comparative Examples 1 to 7

[0069] The preparation method of the comparative example is the same as that of the embodiment, and the specific formula is shown in Table 2.

[0070] Table 2 Fiber-reinforced ultra-high performance concrete (parts by weight)

[0071] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 coarse aggregate 500 500 500 500 500 500 500 fine aggregate 700 700 700 700 700 700 700 Steel Fiber 1 200 Modified steel fiber 1 200 240 Modified steel fiber 5 200 Modified steel fiber 6 200 Modified steel fiber 7 200 Modified steel fiber 8 200 Polyester Fiber1 40 Modified polyester fiber 1 40 40 40 40 40 Silica Fume 90 90 90 90 90 90 90 Water reducing agent 17 17 17 17 17 17 17 cement 750 750 750 750 750 750 750 Fly ash 100 100 100 100 100 100 100 water 180 180 180 180 180 180 180

[0072] A fiber-reinforced ultra-high performance concrete prepared in Examples 1 to 13 and Comparative Examples 1 to 7 was covered with a plastic film immediately after being poured and vibrated into shape and placed at room temperature for 24 hours. After demolding, the test blocks were wrapped with a geotextile and watered for 28 days, and then the following related performance tests were carried out. The results are shown in Table 3.

[0073] 1. Compressive strength test: The specimen size is 100mm×100mm×100mm, and the test method is carried out in accordance with the national standard GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0074] 2. Flexural tensile strength test: The specimen size is 100mm×100mm×400mm, and the test method is carried out in accordance with the national standard GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0075] 3. Fracture energy test: The specimen size is 100mm×100mm×400mm, and the test method is carried out in accordance with the standard test method of “Determination of Fracture Energy of Concrete by Three-Point Bending Beam with Notch”.

[0076] 4. The residual compressive strength, residual flexural tensile strength and residual fracture energy are all residual properties of the specimens under stress-free conditions after being subjected to a high temperature of 500°C.

[0077] Table 3 Performance tests of embodiments and comparative examples

[0078]

[0079]

[0080] It can be seen from the results of the embodiments and comparative examples that by mixing modified steel fibers and polyester fibers, the compressive strength, flexural tensile strength, fracture energy and high temperature residual performance of the concrete matrix are effectively enhanced. It can be seen from the data of the embodiments that the obtained fiber-reinforced ultra-high performance concrete has a compressive strength of ≥160MPa, a maximum compressive strength of 188MPa, a flexural tensile strength of ≥23.4MPa, a maximum flexural tensile strength of 30.1, and a fracture energy of ≥18462J / m 2 , the maximum breaking energy can reach 25468J / m 2 , and the residual performance under stress-free conditions after being subjected to a high temperature of 500°C can maintain more than 65% of the original performance.

[0081] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A fiber-reinforced ultra-high performance concrete, characterized in that: By weight, the raw materials include 400-600 parts of coarse aggregate, 600-800 parts of fine aggregate, 80-200 parts of silica fume, 500-800 parts of cement, 100-200 parts of fly ash, 150-250 parts of modified steel fiber, 20-60 parts of modified polyester fiber, 15-40 parts of water reducer and 150-200 parts of water; The modified steel fiber is a hyperbranched epoxy resin modified steel fiber, and the modified polyester fiber is a gallic acid grafted chitosan modified polyester fiber; The modified steel fiber preparation method comprises the following steps: S1. cleaning the steel fiber and drying it, and performing sandblasting on the surface; S2. adding an aminosilane coupling agent to a mixed solution of ethanol and water and stirring it evenly; adding the steel fiber obtained in step S1 to the solution and stirring it in a water bath at 70-90°C for 30-40 minutes; min, filter and dry to obtain silane-modified steel fiber; S3. Under a nitrogen atmosphere, dissolve citric acid and maleic anhydride in a mixed solution of toluene and 1,4-dioxane, add p-toluenesulfonic acid and stir at 80-95°C for 2-6h to obtain a solution containing citric acid maleate, and remove p-toluenesulfonic acid by vacuum distillation; S4. Add epoxy resin to the solution of citric acid maleate, control the temperature at 115-120°C, stir for 3-4h, and obtain hyperbranched epoxy resin; S5. Add silane-modified steel fiber to the hyperbranched epoxy resin and continue stirring for 20-40min; cool to 80-100°C, add curing agent, and stir for 10-60min to obtain modified steel fiber; The modified polyester fiber preparation method comprises the following steps: S1. dissolving chitosan in an acetic acid solution at room temperature and stirring for 1-3 hours, adding an ethanol solution of gallic acid and a catalyst and continuing stirring for 5-10 hours to obtain gallic acid grafted chitosan; S2. adding polyester fiber to the reaction solution of gallic acid grafted chitosan, stirring at 170-180° C. for 20-60 minutes, cooling to room temperature, filtering and drying to obtain the modified polyester fiber.

2. The fiber-reinforced ultra-high performance concrete according to claim 1, characterized in that: The steel fibers are composed of straight steel fibers and end hook-shaped steel fibers mixed in a mass ratio of (3-6): (4-7); the lengths of the straight steel fibers and end hook-shaped steel fibers are 13-20 mm.

3. The fiber-reinforced ultra-high performance concrete according to claim 1, characterized in that: The sandblasting treatment uses steel shot with a particle size of 0.5-1.5 mm as abrasive; the surface roughness Ra of the steel fiber after sandblasting is 3-6.

4. The fiber-reinforced ultra-high performance concrete according to claim 1, characterized in that: The mass ratio of the citric acid, maleic anhydride and bisphenol A epoxy resin is (3.9-5.9):1:(13.8-20.9).

5. The fiber-reinforced ultra-high performance concrete according to claim 1, characterized in that: Include at least one of the following (i) to (v): (i) the mass ratio of chitosan to gallic acid is 1:(0.5-0.8); (ii) The catalysts used in the reaction of chitosan and gallic acid are 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide; (iii) the curing agent is diaminodiphenylmethane; (iv) the epoxy resin is a bisphenol A type epoxy resin; (v) The polyester fiber has a diameter of 10-30 μm and a length of 6-12 mm.

6. The fiber-reinforced ultra-high performance concrete according to claim 1, characterized in that: The mass ratio of the modified steel fiber to the modified polyester fiber is (4-5):

1.

7. The fiber-reinforced ultra-high performance concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid high-efficiency water reducing agent with a solid content of ≥40% and a water reducing rate of ≥30%; the cement is ordinary Portland cement.

8. The method for preparing fiber-reinforced ultra-high performance concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: Add cement, fly ash, silica fume and 20% water and stir at 48r / min for 2 minutes, then add coarse aggregate and fine aggregate and stir for 2 minutes, then add water reducer and remaining water and stir for 3 minutes, finally add modified steel fiber and modified polyester fiber and continue stirring for 3 minutes before discharging.

Citation Information

Patent Citations

  • Fibrous materials and composites

    AU2013203510A1

  • Ultra-high performance concrete sleeper

    CN112830726A